2021
DOI: 10.3390/foods10040859
|View full text |Cite
|
Sign up to set email alerts
|

A Narrative Review on Dietary Strategies to Provide Nitric Oxide as a Non-Drug Cardiovascular Disease Therapy: Beetroot Formulations—A Smart Nutritional Intervention

Abstract: Beetroot is a remarkable vegetable, as its rich nitrate and bioactive compound contents ameliorate cardiovascular and metabolic functions by boosting nitric oxide synthesis and regulating gene expressions or modulating proteins and enzyme activities involved in these cellular processes. Dietary nitrate provides a physiological substrate for nitric oxide production, which promotes vasodilatation, increases blood flow and lowers blood pressure. A brief narrative and critical review on dietary nitrate intake effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 54 publications
0
20
0
Order By: Relevance
“…In the same line, plasma nitrate/nitrite levels increased significantly in overweight or obese adolescents after 1 h of intake and after a week of daily intake of 50 g of freeze-dried strawberry powder [ 44 ]. Likewise, a reduction in BP and an increase of NO were observed after the consumption of beetroot, spinach, or rocket leaf [ 2 , 8 ], all good sources of nitrates and nitrites, like many other fruits and vegetables [ 8 , 45 , 46 ]. Conflicting results were found in studies with postmenopausal women, or adults with prehypertension or hypertension, in which a daily intake of 150–400 mg nitrate over periods ranging from 10 days to 12 weeks increased NO (measured by nitrate in urine or plasma) but did not reduce SBP or DBP [ 47 , 48 , 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the same line, plasma nitrate/nitrite levels increased significantly in overweight or obese adolescents after 1 h of intake and after a week of daily intake of 50 g of freeze-dried strawberry powder [ 44 ]. Likewise, a reduction in BP and an increase of NO were observed after the consumption of beetroot, spinach, or rocket leaf [ 2 , 8 ], all good sources of nitrates and nitrites, like many other fruits and vegetables [ 8 , 45 , 46 ]. Conflicting results were found in studies with postmenopausal women, or adults with prehypertension or hypertension, in which a daily intake of 150–400 mg nitrate over periods ranging from 10 days to 12 weeks increased NO (measured by nitrate in urine or plasma) but did not reduce SBP or DBP [ 47 , 48 , 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, a diet rich in fruits and vegetables could result in an increase of nitrate, nitrite, and antioxidant, which could contribute to improve cardiovascular health [7,11,12]. Some studies have evaluated the relationship between NO and nitrate intake in adult populations, showing a reduction in blood pressure after a dose of nitrate whether in concentrated solutions or in the form of vegetable-based products [2,8]. However, scarce studies have examined the association between a healthy diet (i.e., fruit and vegetable intake) and urinary NO.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the middle of the 1980s, research has shown that nitrite is a major chemical with substantial impacts on human health. Vegetables are a great source of dietary nitrates, and they have been proven to be an important source of endogenous nitrite as well as nitric oxide (NO) in the human body [ 14 ]. Nitric oxide (NO), produced through enzymatic synthesis, regulates blood pressure, wound healing, immunological response and neurological processes in the human body [ 15 ].…”
Section: Introductionmentioning
confidence: 99%